Regex with ChatGPT - Taulli, Tom 1968- (Shortcuts, 2024)
Whether you're a developer, a creative writer, or business manager, these shortcuts will help you get the most from ChatGPT. Topics include generating content and artwork, developing software code, and building custom GPTs. Each video contains practical tips to help you leverage ChatGPT.